THE EFFECT OF STRATEGIC HUMAN RESOURCES COMPETENCY AND LOGISTIC MANAGEMENT ON ORGANIZATIONAL PERFORMANCE MEDIATED BY STRATEGIC LEADERSHIP - Toto Dwijaya Saputra; Kusnadi Kusnadi (ABNUS Publisher, 2021)
This study aims to investigate the effect of Strategic Human Resources Competency and Logistic Management on Organizational Performance mediated by Strategic Leadership. The methodology used in this study is explanatory research with hypothesis testing to test the seven hypotheses proposed in the study and the population and sample are 180 who serve in Koarmada I. Data collection uses questionnaires and technical data analysis uses SEM (Structural Equation Modeling). Based on the results of hypothesis testing and the discussion in the previous chapter, in general the conclusion is that there are Strategic Human Resources Competence, Logistics Management on Organizational Performance mediated by Strategic Leadership This study shows that Strategic Human Resources Competency and Logistics Management on Organizational Performance are mediated by Strategic Leadership either directly or indirectly. This research is a useful tool to improve Organizational Performance by increasing Strategic Human Resources Competency and Logistics Management and Strategic Leadership. This research model refines the overall understanding that there are direct and indirect effects of Strategic Human Resources Competence, Logistics Management on Organizational Performance mediated by Strategic Leadership.